The Supreme Court Acknowledges Congress’ Authority to Confer Informational Standing in Spokeo, Inc. v. Robins - Bradford C. Mank (Washington University Law Review, 2017)
The Supreme Court’s 2016 decision in Spokeo, Inc. v. Robins does not fully resolve when an intangible injury such as a defendant’s misreporting of a plaintiff’s personal information is sufficient to constitute a “concrete injury” for Article III standing. However, the Spokeo decision makes clear that Congress has a significant role in defining intangible injuries for Article III standing beyond what was considered an injury under the American or English common law. Some commentators had thought Spokeo might overrule the Court’s prior decisions in Akins and Public Citizen, which both held that a plaintiff may have standing based solely upon his statutory right to information. Instead, the Court in Spokeo reaffirmed its informational standing decisions in Akins and Public Citizen.
Keywords: Spokeo; Inc. v. Robins; Article III standing; Concrete injury; Public Citizen v. United States Department of Justice